Mulheres criminosas: transgressão, violência e repressão na Fortaleza do Século XIX - Braga Júnior, Walter de Carvalho (2018)
In this work we looking for analyze the discourses built about the transgressor woman in the nineteenth-century Fortaleza. The way how society, at the time, determined specific spaces and behaviors for men and women found support both control devices such as honor, in the dicoursive web maintained by the legal discourse around the idealized / expected behaviorsfor the masculine and the feminine and in the massifier reach of newspapaer. The newspapers of great circulations at the time, mainly O Cearense and Pedro II bring in their pages the concern of an elite which in addition to modernizing itself seeks to tranform the city into the ideal space for itself, favoring certain behaviors called civilized and extending its watchful eye to the undesirables with which coexixted in the space of the city. It is in this game engedered by the regulatory discourses that murderers, adulterers, prostitutes, madwoman, infanticides are represented with all the force like those that do not represent the feminine nature, become, in the eyes of the public, true beasts and as such, they should be private of social conviviality, incarcerated in prisons or asylum. The figure of the woman fatal to man goes to populate the social imaginary nineteenth-century as echo of a series of negative representations around the feminine that with the advent of the social medicine turn to transform the transgressors not only those who broke the social patterns, but, for escaping from the expected role for their sex, were also treated as abnormal. These abnormals, isolated from the social life, marked by the weight of their transgressions to the role of ideal woman formed the picture that leaves evident, in the contrast between the representations around the ideal women and the others women, the effort in the maintenance of the privileges of the patriarchy, mainly in what it refers to violence, in their physical, moral and symbolic dimensions. In the contrast between representations around the ideal women and the others it is possible to perceive the reinforcement and the maintenance of the privileges of the patriarchy, mainly with regard to violence, in its physical, moral and symbolic dimensions.